A COMPARISON OF UNDERWRITER REPUTATION MEASUREMENT METHODS IN EXPLAINING IPO STOCK PERFORMANCE - Teja, Adrian (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2021)
This study objective compares the underwriter reputation, measured by a different method, in explaining Initial Public Offering (IPO) performance. The reputation is measured based on underwriter IPO frequency and deal value. The underwriter's reputation is then ranked and categorized into quartiles. We use cross-section regression methods to test the effect of different underwriter reputation measurement methods on IPO performance. The dependent variable is short-term and long-term IPO performance. The independent variable is four underwriter reputation categories represented by three-level dummy variables. We found that only underwriter reputation measured by IPO frequency can explain IPO performance. The findings suggest IPO frequency help underwriter understand the market condition and value IPO more accurately. Firms that want to reduce the cost of IPO underpricing should choose underwriters with a higher IPO frequency.